Bioinspired Soft Multistate Resistive Memory Device Based on Silk Fibroin Gel for Neuromorphic Computing. Issue 10 (6th May 2022) - Chougale, Mahesh Y.; Khan, Muhammad Umair; Kim, Jungmin; Shaukat, Rayyan Ali; Saqib, Qazi Muhammad; Patil, Swapnil R.; Dongale, Tukaram D.; Bermak, Amine; Mohammad, Baker; Bae, Jinho
Abstract : Brain‐inspired computation is a promising field toward the next generation of intelligent computing systems. To mimic the brain functions, this field requires devices that can support the goal of computing efficiency, size, and cost. Therefore, researchers are trying to fabricate soft and flexible devices using synthetically organic and inorganic materials like solid‐state or ionic liquids. Herein, a soft and flexible bioinspired neuromorphic computing device based on organic silk fibroin gel, which is robust under external forces, is proposed. Silk fibroin protein is composed of essential and nonessential amino acids. with special amount of positively charged glycine, alanine, which plays an essential role during ionic movement to perform neuromorphic computing. Detailed electrical characterization of the proposed (Cu/silk fibroin gel/Cu) discrete device confirms the synaptic behavior by applying different pulse amplitudes, pulse widths, and frequencies. In addition, the proposed device delivers stable performance during mechanical deformations. The analysis of the present results defines that the proposed device is a potential candidate for environmentally friendly wearable intelligent electronics. Abstract : The organic and biocompatible neuromorphic computing system paves the path toward developing wearable and implantable devices. Herein, the silk fibroin gel‐based synaptic device is proposed, which demonstrates excellent characteristics such as soft, flexible, and biocompatible electronic synapses. According to the results, it is sure that the proposed device is a potential candidate to develop the biocompatible wearable intelligent system.